Concussion and head acceleration event exposure in elite-level English rugby union and American football: interpreting indicative trends - Tierney, G. (Research in Sports Medicine, 2026)
Elite-level American football and rugby union have growing clinical and legal concerns over player safety. A comparison of current indicative trends in concussion and head acceleration events (HAEs) in elite-level American football and English rugby union was undertaken. Elite-level rugby union players have a greater number of professional playing years and matches available in an English season than their American football counterparts. Elite-level rugby union players in England have a greater number of concussions reported per match and a higher proportion of concussions occurring during training sessions, based on National Football League (NFL) and Rugby Football Union (RFU) injury reports. Preliminary findings indicate that elite-level rugby union players in England experience a higher incidence of HAEs per player match over lower and higher magnitude thresholds than American football positional counterparts. Taken collectively, current evidence indicates a trend towards greater reported exposure in elite-level English rugby union across several key metrics.